Unlocking Islamic Finance Potential in Uzbekistan and Central Asia: A Forward-Looking Perspective - Jalilov Mehroj Erkin Ugli; Nugraha Nugraha; Zulayho Umarova (Tazkia Islamic University College, 2026)
This study investigates the socio-demographic determinants influencing public awareness of Islamic finance within the evolving economic landscape of Uzbekistan and the broader Central Asian region. Utilizing a quantitative research design, primary data were harvested from a cross-sectional survey of 400 respondents in 2024. The analytical framework employs descriptive statistics and binary logistic regression to evaluate the predictive power of gender, age cohorts, and educational attainment on Islamic Finance Awareness (IFA). The findings indicate that both age and education level are positively associated with awareness of Islamic finance, while gender shows no significant influence. Logistic regression analysis confirms these results, with education level emerging as the strongest predictor, followed by age. The study underscores the importance of education-based interventions and age-sensitive awareness strategies in promoting the development of Islamic finance in the region.